High dependency units in the UK: variable size, variable character, few in number. Issue 834 (April 1995) - Thompson, F. J.; Singer, M.
Abstract : An exploratory descriptive survey was conducted to determine the size and character of high dependency units (HDUs) in the UK. A telephone survey and subsequent postal questionnaire was sent to the 39 general HDUs in the UK determined by a recent survey from the Royal College of Anaesthetists; replies were received from 28. Most HDUs (82%, n = 23) were geographically distinct from the intensive care unit and varied in size from three to 13 beds, although only 64% (n = 18) reported that all beds were currently open. Nurse: patient ratios were at least 1:3. Fifty per cent of units had one or more designated consultants in charge, although only 11% (n = 3) had specifically designated consultant sessions. Junior medical cover was provided mainly by the on-call speciality term. Twenty units acted as a step-down facility for discharged intensive care unit patients and 21 offered a step-up facility for patients from general wards. Provision of facilities and levels of monitoring varied between these units. Few HDUs exist in the UK and they are variable in size and in the facilities and monitoring procedures which they provide. Future studies are urgently required to determine cost-effectiveness and outcome benefit of this intermediate care facility.